Spremljanje koncentracije askospor glive Eutypella parasitica - Hauptman, Tine (Gozdarski vestnik, 2021)
Fungus Eutypella parasitica originates in North America and causes a disease called Eutypella canker of maple. In Slovenia, it was found for the first time in the year 2005; now it is spread in the whole country and the disease cannot be rooted out anymore. To prevent further spread of the disease and reduce the number of new infections, the infected trees must be cut down. Thereby, the valid instruction requires the infected part of the trunk should be cut out at least 50 cm above and under the wound and that the cut-out part should be burned on the spot or laid on the forest soil in such a way that the canker wound is facing the soil. We wanted to test the effectiveness of the latter measure by monitoring the ascospores of the E. parasitica fungus concentration in the air before the performed measure and after it. Monitoring was not successful; thus, we cannot confirm the effectiveness of this measure. In the article, we present our monitoring methods and discussion about possible reasons for unsuccessful catching of the E. parasitica fungus ascospores.
Keywords: Eutypella canker of maple; Eutypella parasitica; javorov rak; monitoring; Slovenia; Slovenija; volumetric sampler; volumetrični vzorčevalnik